2007
DOI: 10.1080/15622970601169758
|View full text |Cite
|
Sign up to set email alerts
|

The changes of AgNOR parameters of anterior cingulate pyramidal neurons are region-specific in suicidal and non-suicidal depressive patients

Abstract: The anterior cingulate cortex (AC) is consistently implicated in the pathophysiology of depression. While suicide has been shown in previous reports to be closely related to depression, it is still a distinct phenomenon. The aim to differentiate between depression and suicide was approached by the karyometric analysis of AC pyramidal neurons. The study was performed on paraffin-embedded brains from 20 depressive patients (10 of whom had committed suicide) and 24 matched controls. The karyometric parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
12
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 86 publications
7
12
0
3
Order By: Relevance
“…We have recently revealed in a series of publications that processes leading to suicide have an outstanding impact on the observed neurohistological abnormalities independent from the main Axis I diagnosis [1822, 39]. This impact was also accentuated in our previous quantitative study on GAD-ir neuropil in the same cohort [21], where we found an increase in its density specific for depressed suicidal patients from the MDD and BD diagnostic groups.…”
Section: Discussionsupporting
confidence: 54%
“…We have recently revealed in a series of publications that processes leading to suicide have an outstanding impact on the observed neurohistological abnormalities independent from the main Axis I diagnosis [1822, 39]. This impact was also accentuated in our previous quantitative study on GAD-ir neuropil in the same cohort [21], where we found an increase in its density specific for depressed suicidal patients from the MDD and BD diagnostic groups.…”
Section: Discussionsupporting
confidence: 54%
“…These are: AgNOR area (representing the nucleolus), AgNOR number (i.e. the number of AgNOR areas within one nucleus) and AgNOR ratio defined as the quotient of total AgNOR area in the nucleus and nuclear area [9][10][11][12][13][14][15][16][17][18][19][20][21][22] (for reviews see: [23,24]).…”
Section: Introductionmentioning
confidence: 99%
“…Wir haben diese Technik in der Depressionsforschung angewandt, um histologisch Veränderungen der transkriptionalen Aktivität von rDNA in Neuronen darzustellen (ǠTab. ; 6,21,22,24,25,27). Der Grundgedanke unserer AgNOR-Studien war, dass diese Analysetechnik hilfreich für eine vergleichende Interpretation von Post-mortem-und funktionellen In-vivo-PET-und Kernspinstudien sein könnte.…”
Section: Discussionunclassified
“…Diese waren vorwiegend suizidassoziiert und in geringerem Maß auf Unterschiede zwischen Fällen mit unipolarer bzw. bipolarer Depression zurückzuführen (21,24). Der OFK war die einzige untersuchte Hirnregion, in der suizidassoziierte AgNOR-Veränderungen geringer ausfielen, wenn die Patienten in den letzten drei Monaten vor dem Todeszeitpunkt eine Psychopharmakotherapie erhielten.…”
Section: Discussionunclassified